(untitled) (International Seven Journal of Multidisciplinary, 2025)
The article discusses how entrepreneurial leadership can stimulate innovation and strengthen sustainable practices within civil construction, a sector historically marked by traditional processes and little openness to change. The research gathered studies that show that the role of the manager goes far beyond organizing tasks: he directly influences the way teams perceive the importance of reducing environmental impacts and seeking more responsible constructive solutions. Examples of companies that have adopted technologies, certifications and new forms of management were identified, managing to improve efficiency and at the same time consolidate a positive image in the market. The work reinforces that innovation and sustainability cannot be seen as isolated actions, but rather as part of a broader strategy, where leadership becomes an essential support point to transform the internal culture and align economic and environmental objectives.